Breast Feeding Initial Difficulties -descriptive study - Eunice Francisca Martins E. F. Martins; Cármem Mayana Bonfim Esteves Oliveira C. M. B. E Oliveira (Online Brazilian Journal of Nursing, 2006)
This study aimed at identifying initial difficulties in breastfeeding in a rooming-in care. An assessment of ninety newly-born`sucking was carried out, using UNICEF standard protocol. Observation revealed that most mother-infant pairs presented favorable behaviours towards breastfeeding, and indicatory signs of difficulties were more evident in relation to sucking and to breast response. Care in collective wards should aim at overcoming these difficulties as to facilitale the beginning of breastfeeding, thus favoring its continuity.